A Comprehensive Novel Stability indicating Method Development and Validation for Simultaneous Assessment of Abiraterone and Niraparib in Bulk and Pharmaceutical Formulation by Ultra Performance Liquid Chromatography - Anusha, Gandi; Pawar, Krishnamanjari (Jordan Journal of Pharmaceutical Sciences, 2025)
Background: This study aims to develop and validate an innovative, rapid and dependable reverse-phase Ultra Performance Liquid Chromatography method for the simultaneous quantification of the anticancer drugs Abiraterone and Niraparib in bulk and pharmaceutical formulations marketed under the brand name Akeega. By offering a precise and stability-indicating assay, this research addresses a critical need for efficient analytical methods to assess these two agents in combination, an area with limited prior exploration. This novel approach not only fills a significant gap in the quantification of these compounds but also enhances analytical reliability for combined anticancer therapies, supporting broader research and quality control efforts. Method: The method was optimized for isocratic elution on a C18 HSS column (2.1 mm × 100 mm, 1.8 μm) using a mobile phase composed of methanol and buffer 60:40v/v at a flow rate of 0.3 mL/min providing stable performance at room temperature. Detection was carried out with a UV detector set to 259 nm using a 10 μL sample injection volume and a total run time of five minutes. Results: The retention times for Abiraterone and Niraparib were observed at 1.0333 and 3.4833 minutes, respectively, demonstrating excellent peak separation and resolution. The method showed strong linearity within concentration ranges of 12.5–75 μg/mL for Abiraterone and 2.5–15 μg/mL for Niraparib with calibration curve regression equations of Y = 9668x - 3531 (R² = 0.999) for Abiraterone and Y = 9632x + 1803 (R² = 0.999) for Niraparib. The % RSD values indicating precision were below 2 at 0.239 and 0.265. The method yielded percentage mean recoveries of 99.4-99.7% for Abiraterone and 99.5-99.8% for Niraparib with % RSD values ranging from 0.1-0.2 and 0.1-0.3 respectively. Rigorous forced degradation tests, including acidic, alkaline, oxidative, photolytic, and thermal conditions, confirmed the method’s effectiveness as a stability-indicating assay. Conclusion: Following validation in alignment with International Council for Harmonization (ICH) guidelines the method was found to be linear, specific, accurate, robust, time-efficient and suitable for quality control and process monitoring in the bulk manufacturing of these drugs. This validated method offers a valuable tool for ensuring the quality and stability of Abiraterone and Niraparib supporting their development and regulatory compliance.